Fundamental understanding of voltage decay in Li-rich Mn-based layered oxides cathode materials - Huixian Xie; Jiacheng Xiao; Hongyi Chen; Boyang Zhang; Kwun Nam Hui; Shanqing Zhang; Chenyu Liu; Dong Luo; Zhan Lin (AAPPS Bulletin)
Abstract To satisfy the needs of modern intelligent society for power supplies with long-endurance ability, Li-rich Mn-based layered oxides (LRMOs) are receiving much attention because of their ultrahigh capacity. However, their real-world implementation is hindered by the serious voltage decay, which results in a continuous decrease in energy density. The understanding on voltage decay still remains a mystery due to the complicated hybrid cationic-anionic redox and the serious surface-interface reactions in LRMOs. Moreover, some of the mechanisms are occasionally contradictory, indicating that the origin of voltage decay is still unclear. As a result, none of the innovative strategies proposed on the basis of mechanisms has effectively alleviated the problem of voltage decay, and voltage decay becomes a long-term distress of LRMOs. Therefore, it is particularly crucial to sort out the mutual relation of various mechanisms, which helps to go back to the source of voltage decay. In this review, we summarize the current mechanisms of voltage decay as structural evolution and oxygen chemistry, and attempt to trace the origin of voltage decay for LRMOs. In addition, we discuss how current researches address the issue with generalized guidance in designing appropriate strategies based on mechanisms.